Design and initial testing of a maize cob collection system - Dolšak, Bojan; Breznik, Anita; Kaučič, Klemen; Imenšek, Nataša; Marčec, Marko; Gselman, Peter; Humar, Jani; Krajnc, Mitja (International Journal of Agricultural and Biological Engineering, 2024)
Maize cobs are valuable plant residues that can be used for many different purposes, including as a renewable energy source. Despite their value, maize cobs are still underutilized, mainly because people are not aware of their potential and harvesting techniques for their collection are still being developed. Therefore, this research focused on finding the most suitable energy- and time- efficient method for mechanical collection of maize cobs. Upgrading the combine harvester with an additional hopper proved to be the most promising solution, as it allows harvesting and storage of maize grain and maize cobs in one pass, while the harvesting time remains almost the same and the maize cobs are of good quality, as they do not fall on the field. A prototype with enlarged openings in the straw walkers, an additional grab container for maize cobs, a transport auger, a transport cleaning fan with built-in knives, a transport tube and some other assemblies was fabricated and used in practice. The first test results are very encouraging (94.4%-96.0% purity of maize cobs) and the system has been patented as a promising solution, especially in times when the environmental sustainability of the planet and energy independence are becoming increasingly important. Keywords: maize cobs, utilization, mechanical harvesting, combine harvester upgrade DOI: 10.25165/j.ijabe.20241703.8218 Citation: Dolšak B, Breznik A, Kaučič K, Imenšek N, Marčec M, Gselman P, et al. Design and initial testing of a maize cob collection system. Int J Agric & Biol Eng, 2024; 17(3): 108-114.